Evaluation of the innovative value proposition for the rail freight transport: an integrated DEMATEL–ANP approach - Milenković, Miloš; Val, Susana; Lutovac, Dejan; Bojović, Nebojša; Knežević, Nikola (Transport, 2021)
Freight transport represents a very dynamic and competitive market with high requirements for reliability, lead time, cost, flexibility and visibility of transport service. Rationalization of transport service, reduced travelling time and reliable delivery times represent the main prerequisites for lowering the costs and increasing the efficiency of entire transport chain. These performance indicators actually represent the main factors affecting the shipper’s mode choice. Improvement of these factors could be achieved by improved coordination between rail and non-rail-related stakeholders involved in freight transport service planning and realization. Since this solution requires a multi-stakeholder collaboration, it is needed to evaluate the interests of each of them in order to derive a preferred set of indicators, which will facilitate a collectively accepted solution and value alignment of all involved actors. In this paper, the preferred set of indicators was selected by using the DEcision MAking Trial and Evaluation Laboratory (DEMATEL) model technique integrated with the Analytic Network Process (ANP). DEMATEL is applied to analyse the causal relationships among the relevant dimensions and among the criteria within each dimension. The causal relationships are then used in ANP for determining the weights of the criteria. An empirical case study based on implementation of information sharing platform in rail intermodal transport chain is presented to demonstrate the effectiveness of the proposed approach. Based on this study the attributes that belong to reliability (“departing / arriving on-time”, “cancelled services”), lead time (“idle time”) and investment cost (“organizational culture”, “business process redesign”) dimensions represent five the most critical factors for obtaining a collectively accepted solution. This effective evaluation model enables policy makers and stakeholders in transportation / logistics to understand and conduct appropriate actions towards fulfilling the objectives for greener transportation.First published online 2 April 2021